Structural electrochemistry and biomimetic sensing characteristics of polyindole and poly (3,4-ethylenedioxythiophene) based materials - Lijin Rajan (Department of Chemistry University, of Calicut, 2024)
Biological muscles possess the remarkable ability to sense energetic working conditions such as temperature, pressure, chemical potential, and muscle potential while working. These muscles function as macromolecular machines triggered by electrical signals from the brain via connecting neurons, with feedback signals sent back to the brain through sensing neurons, forming a brain-muscle interface; a two-wire communication system. Mimicking this brain-muscle interface has long been a challenge for scientists. However, decades of research led to the development of a model using conducting polymers as biomimetic reactive materials, capable of simulating the sequential reactions in biological muscles. In this work, we investigated the reactive sensing behaviour, reversible conformational movements, and electrochemically induced structural changes of conducting polymers controlled by a computer, with feedback transmitted through the same wires, akin to biological systems. This research aimed to fulfil an engineering aspiration: building devices that can simultaneously perform work and sense their environment by delving into the fundamental electrochemistry of conducting polymers. Two conducting polymers, polyindole (PIN) and poly(3,4-ethylenedioxythiophene) (PEDOT), were selected for this study. Our group had previously explored the reactive sensing properties of polypyrrole and polyaniline. With this study of PIN and PEDOT, we aimed to establish that sensing the environment while working is a general property of conducting polymers. To achieve this, we synthesized PIN using chemical oxidative polymerization and examined its structural electrochemistry, including the conformational changes in the polymer chains during electrochemical reactions and the associated charge consumption. The redox potential of these polymers was determined, and their reactive sensing capabilities were demonstrated through electrochemical techniques such as chronopotentiometry and cyclic voltammetry. To overcome the limitations of using polymer powders in device fabrication, we developed a free-standing electroactive composite film, PIN/PVA, using polyvinyl alcohol hydrogels. The reactive sensing ability of this film was studied, and we introduced the concept of cooperative actuation, where reversible conformational movements of polymer chains enable environmental sensing during working. This mechanism was likened to the reversible conformational changes in sarcomeres in biological muscles, which are critical to their sensing properties. Similarly, cooperative actuation in conducting polymer chains was identified as the key factor behind their sensing abilities. Building on this concept, we synthesized PEDOT and studied its structural electrochemistry and sensing properties. A PEDOT/PVA film was fabricated, and its sensing ability was validated through cooperative actuation. Additionally, we investigated the supercapacitor properties of this film, demonstrating its ability to sense electrical working conditions while simultaneously storing and discharging charge. A solid-state, two-electrode device was fabricated using the PEDOT/PVA film, and its supercapacitor performance and reactive sensing abilities were evaluated. This device showcased the capability of sensing working conditions during charging and discharging using only two connecting wires. In conclusion, this research partially realized the long-standing engineering goal of creating sensing motors that can simultaneously perform work and monitor their environment.
Keywords: Conducting polymer; Actuators Biomimetic; Polyindole